2023
DOI: 10.1111/jfpe.14282
|View full text |Cite
|
Sign up to set email alerts
|

Processing of encapsulated flaxseed oil‐rich banana‐based (Dwarf cavendish) functional fruit leather

Abstract: Banana fruit leather enriched with flaxseed oil in the form of encapsulates was prepared. Initially, the optimized conditions of 836 W power for 4 min for blanching of banana using microwave were obtained by Response Surface Methodology with residual polyphenol oxidase activity and vitamin C retention taken as responses. The addition of maltodextrin, citric acid, and pectin for blending with banana puree to obtain a non sticky puree having low pH was also optimized, while keeping the quantity of sugar constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Fresh fruits are perishable and have a relatively short shelf life (Amit et al ., 2017). Many studies have reported on making fruit leather to utilise perishable seasonal fruits (Sharma et al ., 2016; Eyiz et al ., 2020; Das et al ., 2021) and to produce functional foods (Sarma et al ., 2023). Fruit leathers are restructured fruit products with a soft and chewy texture, resembling soft leather (Diamante et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Fresh fruits are perishable and have a relatively short shelf life (Amit et al ., 2017). Many studies have reported on making fruit leather to utilise perishable seasonal fruits (Sharma et al ., 2016; Eyiz et al ., 2020; Das et al ., 2021) and to produce functional foods (Sarma et al ., 2023). Fruit leathers are restructured fruit products with a soft and chewy texture, resembling soft leather (Diamante et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the ripening process of bananas and how to determine their state of ripening plays an important role in ensuring the quality of bananas, reducing losses and waste, and improving economic benefits. Banana is an important crop in subtropical and tropical regions and has a great influence on the world economy (Masithoh et al, 2021; Sarma et al, 2023; Subedi & Walsh, 2011). China is an important banana producer in the world.…”
Section: Introductionmentioning
confidence: 99%